NEUROLOGICAL MANIFESTATIONS OF COVID-19 IN PATIENTS ADMITTED AT A TERTIARY CARE HOSPITAL IN PUNJAB, PAKISTAN - Shafait, Saima; Alamgir, Wasim; Yousaf, Muhammad Ali; Manzar, Muhammad Adnan; Khattak, Abdul Latif; Yousaf, Muhammad Javad (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the frequency of neurological manifestations and complications of SARS-COV-2. We were especially concerned with the cases where the primary presentation was neurological indicating the neuro-invasive potential of the virus.Study Design: Prospective observational study. Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi, from Apr to May 2020.Methodology: A total of 405 confirmed COVID patients were enrolled for the study. Demographic features and initial clinical manifestations were noted and patients were followed during the hospital stay for the development of any new neurological signs and symptoms. For analytical purposes, neurological presentations were grouped into the central nervous system, peripheral nervous system, and musculoskeletal system manifestations. Appropriate laboratory testing was employed as required on case to case basis.Results: In this study, the mean age was 46.6 ± 15.5 years. Two hundred and seventy one (66.9%) patients were male while one hundred and thirty four (33.1%) were female. The neurological illness was a primary manifest-tation in twenty four (6%) cases. These included encephalopathy (n=15), ischemic stroke in young (n=2), Guillain-Barre syndrome, (n=1), facial nerve palsy (n=2), and encephalitis (n=1). The most common neurological symp-toms were headache 142 (35%), and hyposmia 39 (9.6%) followed by encephalopathy 34 (8.3%). More serious complications like seizures 7 (0.7%) and stroke 9 (2.2%) were also seen.Conclusion: Severe Acute Respiratory Syndrome-Coronavirus 2 can present with a neurological illness like its predecessors. We should remain vigilant to the possibility of neurological presentation of COVID-19 that can be thromboembolic, inflammatory or immune-mediated.